Advances in the systematics of the spider genus Troglohyphantes (Araneae, Linyphiidae). Issue 4 (4th July 2017) - Isaia, Marco; Mammola, Stefano; Mazzuca, Paola; Arnedo, Miquel A.; Pantini, Paolo
Abstract : With 128 described species and five subspecies, the spider genus Troglohyphantes (Araneae, Linyphiidae) is a remarkable example of species diversification in the subterranean environment. In this paper, we conducted a systematic revision of the Troglohyphantes species of the Italian Alps, with a special focus on the Lucifuga complex, including the description of two new species ( T. lucifer sp. nov. and T. apenninicus n. sp.). In addition, we provided new diagnostic drawings of the holotype of T. henroti ( Henroti complex) and established three new synonymies within the genus. The molecular analysis of the animal DNA barcode confirms the validity of this method of identification of the Alpine Troglohyphantes and provides additional support for the morphology based species complexes. Finally, we revised the known distribution range of additional Troglohyphantes species, as well as other poorly known alpine cave-dwelling spiders. Troglohyphantes lucifer http://www.zoobank.org/urn:lsid:zoobank.org:act:AB4B644A-D18A-4EB7-99E7-B5117AED5389 Troglohyphantes apenninicus http://www.zoobank.org/urn:lsid:zoobank.org:act:3C86E78E-7145-4F0C-803E-2A909201579C